Stigmatization and racial selection after September 11, 2001: Self-identity among Arab and Islamic Americans - Patrick L. Mason; Andrew Matella (IZA Journal of Migration, 2014)
During the 2000s Arab and Islamic American racial identity selection was subjected to an exogenous racializing event, viz., public and private reaction to the Al Qaeda attacks of September 11, 2001. The Al Qaeda attacks clearly demarcate a period in which there was a structural increase in the intensity of US stigmatization of persons with Islamic religious affiliation and Arab ethnicity. This stigmatization created an exogenous reduction in the expected payoff to acculturation relative to non-acculturation. This paper uses self-identification as white as its measure of acculturation and the fraction of all hate crimes directed at Muslims as its measure of stigmatization after 9/11. Comparing 2002 - 2012 to 1996 - 2001, there is a statistically significant and substantively large decrease in the unconditional and conditional probabilities that Arab and Islamic Americans will self-identify as white. The data are combined cross sections of the Current Population Survey Annual Social and Economic Supplement.
Keywords: J11; J15; Z13; 330; Race; Identity; Arab; Muslim; Islam; September 11.